EFFORTS TO USE TECHNOLOGY EFFECTIVELY IN SUPPORTING THE IMPLEMENTATION OF EDUCATIONAL SUPERVISION - Siti Kabariah; Adiyono (Indonesian Journal of Education (INJOE), 2022)
It is undeniable that the use of technology in today's era has made educators literate about technology. Of course there needs to be guidance from a supervisor so that the technology used can facilitate learning to be as effective as possible. Effective technology will help complete the task of an educator. Science and Technology (Science and Technology) requires us as educators to continue learning. If we are a little careless in learning, we will certainly be left behind by technological developments, including the students being taught. In this study, we used the type of library research research, where the sources used were from someone who had conducted a study, of course, from various journals that were used as references. This study uses a qualitative approach. The focus of learning supervision objectives is the income of learning objectives which are the responsibility of the principal and teacher. Boss positions include: Researcher, Consultant or Advocate, Provider, Motivator, Innovation Pioneer. A supervisor must have the competence to guide and motivate teachers to use technology in learning, in order to achieve effective and efficient educational goals. Teachers and other learning resources are responsible for controlling teaching activities. In this case, the classroom teacher controls students' discipline and interest in learning, while the supervisor is only responsible for guiding and motivating the teacher.